Pengaruh Kepribadian Pendeta Terhadap Minat Kebaktian Minggu Pada Jemaat Di Gereja Pantekosta Isa Al Masih Medan Helvetia - Siregar, Nurliani Siregar; Esra br Ginting; Bangun (LPPM Institut Pendidikan Nusantara Global, 2025)
The purpose of this study was to see how the influence of the personality of the pastor on the interest in Sunday services in the congregation at the Pentecostal Church of Isa Al Masih Medan Helvetia. This type of research is qualitative research with the research population being some of the congregation and pastors at the Pentecostal Church of Isa Al Masih Medan Helvetia. Where in this study using qualitative descriptive. Data collection in this study used observation and interview methods. The interview technique was carried out in a structured manner using the interview method. The analysis of the research data was descriptive. After conducting the research, the results of this study indicate that the personality of the pastor greatly influences the interest of the congregation in the Sunday service at the Isa Al Masih Pentecostal Church in Medan Helvetia. The personality of the pastor in this church shows that his personality greatly influences the interest of the congregation in the Sunday service. The congregation who are experiencing struggles begin to be approached by the pastor and the church will conduct Bible study for the congregation and this is also used by the pastor to approach the congregation.